PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALY, REPETITION (AIR) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 37 PEKANBARU - Weni Putri Ramadani; Syahrilfuddin '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning science study class III SD Negeri 37 Pekanbaru. KKM achieved by school was 80. From 38 students who achieve KKM just 16 students (41,12%) while students who did’nt achieve KKM is 22 students (58,88%) with a class average of 68,89. The purpose of this research to improve learning outcomes IPS class III SD Negeri 37 Pekanbaru with the application of learning models Auditory, Intellectualy, Repetition (AIR). The results obtained by the average value of 68,89 basic score increased in the first cycle of 1,98% to 70,26. In the second cycle the average value of students also increased by 32,92% to 91,57. On the basic of classical completeness score IPS student learning outcomes is only 41,12% (not finished). After the professor of applied learning model Auditory, Intellectualy, Repetition (AIR) in the first cycle classical completeness increased to 44,73% (not finished), and the second cycle of classical completeness obtained are increased to increase to 89,47%. Activities of teachers at the first meeting of first cycle acquire a percentage of 75% with enough categories. The second meeting increased to 83,33% in enough categories. In the first meeting of second cycle increased to 95,83% with good category. At the second meeting increased to 95,83% with good category. Activities of students in the first meeting of the first cycle acquire a percentage of 66,7% with enough categories. The second meeting increased to 75% in enough categories. In the first meeting of the second cycle increased to 87,5% with good category. At the second meeting increased to 95,83% with good category.Keywords : Auditory, Intellectualy, Repetition (AIR), learning outcomes IPS